The Ihsan Hadith as The Spiritual Foundation of Muraqabah: A Comparative Study with Contemporary Mindfulness - Nurhakim, Amien; Andi Rahman, (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This study investigates muraqabah as an Islamic form of mindfulness by analyzing the Hadith of Ihsan (Hadith of Jibril) as recorded in Sahih Muslim. Employing a qualitative methodology grounded in a subjective hermeneutic approach, the study interprets ihsan as a theocentric mode of consciousness defined by continuous awareness of divine presence and oversight, articulated in the prophetic statement: “To worship Allah as though you see Him; and if you do not see Him, then know that He sees you.” The findings demonstrate that while muraqabah shares functional similarities with contemporary mindfulness, such as enhancing inner tranquillity, emotional regulation, and attentiveness, it is fundamentally distinct in its transcendental orientation toward Allah. Rather than self-referential awareness, Islamic mindfulness is rooted in divine awareness (muraqabah), sincerity (ikhlas), and spiritual intensity, positioning consciousness within a relational and ethical framework. Core religious practices, including prayer (salah), Qur’anic recitation, remembrance (dhikr), and self-accountability (muhasabah), function as practical mechanisms for cultivating mindfulness within the paradigm of ihsan, deepening devotion and moral sensitivity. Unlike secular mindfulness approaches, which primarily prioritise psychological well-being and stress reduction, muraqabah integrates spiritual, ethical, and psychological dimensions within a holistic Islamic worldview. The study further highlights the relevance of Ihsan-based mindfulness for contemporary Islamic psychospiritual and therapeutic contexts, particularly in addressing anxiety and fostering emotional balance. Ultimately, this research affirms that the Hadith of Ihsan constitutes the foundational framework for muraqabah, offering comprehensive guidance for both the spiritual cultivation and social conduct of Muslims in modern life.